UJI AKTIVITAS ANTIOKSIDAN DENGAN METODE PEREDAMAN RADIKAL BEBAS DAN SITOTOKSIK DENGAN METODE BRINE SHRIMP LETHALITY TEST (BSLT) AKAR BAJAKAH (Uncaria tomentosa (Willd ex Schult). DC) - Jamiatul Hasanah (PROSIDING SEMINAR KIMIA, 2020)
The root of the Bajakah (Uncaria tomentosa (Willd ex Schult.) DC is one of the plants found on the island of Borneo. People consume its roots to treat cancer. This research has been carried out in several stages, namely by extraction, partitioning, phytochemical screening, antioxidant test with free radical reduction method abd cytotoxic test using the BSLT method. The results showed that the phytochemical sceening of the Bajakah root contained alkaloids, flavonoids, triterpenoids, and steroids, saponins and tannins. The antioxidant activity of the ethyl acetate partition has percent inhibition of 72,61%, for ethanol 96% 74,40% and 77,67% in water. The cytotoxic test on the ethyl acetate partition was 48,39 ppm and the water partition was 354,20 ppm. Keywords : Bajakah, Antioxidant, Cytotoxic